The Mirror of the Grotesque on the Threshold of ‘Dream’: The Polyphony of Fantastic Realism in the Double by F. M. Dostoevsky (Slavic Studies, 2024)
This study hermeneutically examines fantastic realism as a syncresis of the romantic fantastic and the conventions of realism in the novel The Double by F.M.Dostoevsky. The study intends, by evoking the theoretical premises of Tzvetan Todorov and M. M. Bakhtin , to elucidate the interferences of the genres and the narratological strategies through which the paradigm of the double transcends, primarily–through the language of the grotesque and the amalgam of dream and reality. Hence, this study attempts to unveil all the hermeneutically hidden meanders throughout the novel in which the topos of dualism of individuality is polyphonically mirrored.